Opposite Regulatory Effects of Immobilized Cations on the Folding Vs. Assembly of Melittin - Yu, Lanlan; Deng, Zhun; Zhang, Wenbo; Liu, Shuli; Zhang, Feiyi; Zhou, Jianjian; Ma, Chunhua; Wang, Chenxuan (Frontiers in Chemistry, 2021)
Ions play a crucial role in modulating the secondary and tertiary structure of a protein. For the free ions in bulk solution, ammonium is kosmotropic (structure-forming) and guanidinium is chaotropic (structure-breaking) to protein structure within the Hofmeister series. However, the effect of immobilized ions on a protein surface is less explored. In this study, we explored the influence of two immobilized cations (ammonium in the side chain of lysine and guanidinium in the side chain of arginine) on the folding and assembly of melittin. Melittin adopts an amphiphilic alpha-helix structure and is driven by hydrophobic residues packing to associate into a helical bundle. To test the influence of immobilized cations on peptide/protein structure, we designed the homozygous isomers exclusively containing ammonium (melittin-K) or guanidinium (melittin-R) and compared the differences of melittin-K versus melittin-R in their folding, assembly, and molecular functions. The side chains of lysine and arginine differ in their influences on the folding and assembly of melittin. Specifically, the side chain of R increases the alpha-helical propensity of melittin relative to that of K, following an inverse Hofmeister series. In contrast, the side chain of K favors the assembly of melittin relative to the side chain of R, which is in line with a direct Hofmeister series. The opposite regulatory effects of immobilized cations on the folding and assembly of melittin highlight the complexity of the noncovalent interactions that govern protein intermolecular architecture.